The experimental studies of operating modes of a diesel-generator set at variable speed - Obukhov S. G. Sergey Gennadievich; Plotnikov I. A. Igor Aleksandrovich; Surkov M. A. Michael Aleksandrovich; Sumarokova L. P. Liudmila Petrovna (Electric Drive in Mechanical Engineering, 2017)
Title screen